Modeling of environmental risks caused by the spillage of fuels aroused in the Polytucture Esmeraldas - Santo Domingo de Los Tsachilas Case PK-128 from “Eppetroecuador” - Yaulema Garcés, Fausto (2017)
The purpose of this paper was the modeling of risks due to a fuel spill in the coastal region of Ecuador. Fuel spills are an imminent danger due to the impossibility of controlling them immediately because they represent a high destructive potential for the environment. It is hypothesized that a risk management system would allow better understanding in the case of future spills; for this purpose, it is proposed to use UNE 150008 2008 ENVIRONMENTAL RISK ASSESSMENT in addition to geoelectric prospecting. The spill study area comprised approximately 20 hectares of land comprised of the easement belt or right-of-way of the Poliducto and the Pipeline as well as the lands adjacent to the site of the spill where presumably the pollution spread. Through the physical chemical characterization of water, flora, fauna and socioeconomic soil, the results were evaluated using the flow model and the risk - probability matrices, with a value of 17 equivalent to an average of 82% on the human and natural environment corresponds to a serious scenario; while the socioeconomic environment is in the moderate scenario with a value of 14 equivalent to an average of 42%. A model of prevention of environmental risks was adapted to the analyzed conjuncture and a characterization by reduction of dimensions that presented contamination by both heavy metals and by Hap's.The results demonstrated that the human and natural environment presented a grave stage with a value of 17 equivalent to an average of 82%. On the other hand, the socio-economic environment resulted in a moderate scenario. These results leads to the formulation of prevention model of environmental risks, which involves the identified dangers.